Picroside II protects the blood-brain barrier by inhibiting the oxidative signaling pathway in cerebral ischemia-reperfusion injury. - Li Zhai (PLoS ONE, 2017)
BACKGROUND AND PURPOSE:Thrombolysis is used to improve cerebral circulation; at the same time, neuroprotective drugs such as antioxidants should also be used. The aim of these experiments was to explore the protective mechanism of an antioxidant, picroside II, on the blood-brain barrier (BBB) after cerebral ischemia-reperfusion (CI/R) injury. METHODS:To observe the antagonistic effect of picroside II on CI/R damage, the neurological deficit score and the infarct volume were measured. To detect the protective effect of picroside II on nerve cells and the BBB, the morphology and structure of cortical brain tissue were observed, respectively. To investigate the antioxidant effect and mechanism of picroside II, reactive oxygen species (ROS) content, the activity of Nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase), and the protein levels of Nox2 and Rac-1 were detected. To investigate the protective mechanism of picroside II on the BBB, the levels of ROCK, MLCK, MMP-2 and claudin-5 were tested. RESULTS:A higher neurological score, bigger cortex infarction, more damaged neuron structure and injured BBB, increased content of ROS and activity of NADPH oxidase, higher protein levels of Nox2, Rac-1, ROCK, MLCK and MMP-2 and lower levels of claudin-5 were observed in the model group. In the picroside group, the neurological score, neuronal damage, BBB injury, ROS content and NADPH oxidase activity were reduced (P<0.05), and the protein levels of Rac-1, Nox2, ROCK, MLCK and MMP-2 were down-regulated (P<0.05), while the expression of claudin-5 was up-regulated (P<0.05). CONCLUSIONS:Picroside II could protect the nervous system possibly through reducing the content of ROS by down-regulating the expression of Rac-1 and Nox2 and could protect the BBB through reducing the expression of ROCK, MLCK, and MMP-2, while enhancing the expression of claudin-5.